Contrasting views on Antarctic tourism: ‘last chance tourism’ or ‘ambassadorship’ in the last of the wild - Vila, Mar; Costa, Gerard; Angulo-Preckler, Carlos; Sardá, Rafael; Àvila, Conxita (Journal of Cleaner Production, 2016)
10 páginas, 10 tablas Some of the suggested critical issues for Antarctic tourism include the role played by tourists as the last chance to see the icecaps before they melt, or represent potential ‘ambassadors’ within IAATO's (International Association of Antarctica Tour Operators) scope for self-regulation. The study also addresses the question of whether ‘ambassadorship’ evolves in practice from ‘last chance tourism’ and how it evolves. The article urges Antarctic tourism stakeholders to maintain the integrity of the ecosystem while delivering social and economic value. We carried out in-depth interviews of stakeholders and in situ interviews of tourists visiting Antarctica, in order to explore their perceptions from an interdisciplinary perspective based on management and biology. A study of tourist and stakeholder opinions and a combination of the two methods provided a wide perspective on the ‘ambassadorship’ concept. Our findings reveal that the spontaneous trust characterising ambassadorship is far removed from the perception of tour operators. While a trip to Antarctica modifies the opinions of tourists, such changes in perspective are not always favourable to ecological practices. The ambassadorship role played by tourists visiting Antarctica is unclear. This is an exploratory study that develops the debate on whether tourists should be ambassadors for the Antarctic and points to the need for self-regulation to improve stakeholder engagement in protecting the continent. We suggest that a combination of new agreements for the protection of the territory, better planning, the use of management tools, and an improvement in some educational aspects of tourism may help protect Antarctica. Peer reviewed